Peer Feedback: Its Quality and Students’ Perceptions as a Peer Learning Tool in Asynchronous Discussion Forums - Alcuin Ivor Mwalongo (International Journal of Evaluation and Research in Education (IJERE), 2013)
The study examined two aspects, namely the quality of peer feedback in asynchronous discussion forum when such peer feedback is used as a formative learning tool, i.e. not for assigning grades; and students’ perceptions about the process of peer feedback. Twenty four students enrolled in higher education were involved. They were assigned two tasks. In the first task, they contributed lessons learnt about the course on the learning management system, Moodle, via the asynchronous discussion forum. Thereafter they read the comments posted by their colleagues and critiqued them.In the final task that was given at the end of the course, students wrote reflections about peer feedback process. Thus all data collected were in the form of posts. Using NVivo, the posts generated in the first task were used to examine the quality of peer feedback, while the posts generated from students’ reflection about peer feedback were used to examine students’ perceptions about peer feedback. Results indicate that peer feedback is a useful tool for formative learning as well as assessment purposes. Future research could involve a larger sample, a diverse population, and a range of other courses.DOI: http://dx.doi.org/10.11591/ijere.v2i2.1821